Discrepancies in Hospital Cost and Indonesia's Case-based Groups: A Literature Review - Skarayadi, Oskar; Endarti, Dwi; Satibi, Satibi; Mukti, Ali Ghufron (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: Indonesia started establishing national health insurance in 2014. Implementation of Indonesian national health insurance has frequent gaps between health expenditures based on hospital tariffs and the INA-CBG tariffObjectives: This review was aimed to compare the hospital tariff of healthcare to the INA-CBGs tariff and to identify the factors contributing to the actual cost.Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology followed in this research. The keywords